A Survey of Hand Gesture Dialogue Modeling For Map Navigation - Yee Yong Pang; Nor Azman Ismail (Computer Engineering and Applications Journal, 2012)
Human trends to use hand gesture in communication. The development of ubiquitous computer causes the possibility of human to interact with computer natural and intuitive. In human-computer interaction, emerge of hand gesture interaction fusion with other input modality greatly increase the effectiveness in multimodal interaction performance. It is necessary to design a hand gesture dialogue based on the different situation because human have different behavior depend on the environment. In this paper, a brief description of hand gesture and related study is presented. The aim of this paper is to design an intuitive hand gesture dialogue for map navigation. Some discussion also included at the end of this paper.